The Q-NPT: Redefining Nuclear Energy Governance for Sustainability - Hassan Qudrat-Ullah (Energies)
Global peace, security, and sustainable energy development depend on effective nuclear energy governance. While the Nuclear Non-Proliferation Treaty (NPT) has served as a cornerstone in this domain, it faces challenges such as trust deficits, inequitable access to nuclear technologies, and regional instability. This paper proposes the Qudrat-Ullah Nuclear Peace and Trust (Q-NPT) framework, a dynamic implementation roadmap designed to address these issues. The framework focuses on fostering trust among stakeholders, ensuring equitable access to nuclear technologies, and promoting inclusivity in governance structures. A key theoretical contribution is the integration of trust-building measures with sustainable energy transitions, highlighting nuclear energy’s role in decarbonization and global energy security. The paper outlines actionable pathways for implementing the Q-NPT framework, including enhanced oversight by the International Atomic Energy Agency (IAEA), capacity-building initiatives, and training programs to enable safe and sustainable nuclear cooperation, particularly in developing nations. By operationalizing nuclear programs through this approach, the Q-NPT framework aligns nuclear energy governance with global sustainable energy objectives.